PENERAPAN MEDIA PEMBELAJARAN KOMIK STRIP UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATA PELAJARAN IPS TERPADU PESERTA DIDIK KELAS IXC MTs SHOLIHIYYAH KALITENGAH - Sofyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Fun learning will arouse students' motivation, because students will not feel bored and will actually feel interested in learning activities. Motivation has a significant role in determining the outcome of the learning process. Comic strip learning media in education can be applied in integrated social studies learning on the subject of socio-cultural change because comic strips can provide an interesting and funny atmosphere so that students feel happy and more enthusiastic in carrying out teaching and learning activities. student learning outcomes with the application of the Comic Strip learning media on integrated social studies subjects on the material of Socio-Cultural Change. The results show that after learning by applying comic strip media the motivation of students has increased compared to when they have not used comic strip media and based on daily test analysis, the average value of students shows an increase. Before the application of comic strip media in learning the average value achieved was 78.98 while after the application of comic strip media it increased by 6.77% to 84.30.